The Effect of Participatory Budgets on The Performance of School (Studies in Smk Sumbawa) - Aisyah, Siti Nur; Sutrisno, Sutrisno; Saraswati, Erwin (Universitas Negeri Malang, 2017)
This study was aimed to empirically analyze the effect of participatory budgeting on the schoolâs performance with organizational commitment, organizational culture, and leadership styles as the moderating variabels. The populations in this study are educators, educational personnel, committe of 801 people and spread at the vocational high schools in Sumbawa regency comprising 17 private and public schools. The disproportionate stratified simple random sampling was used as sampling technique. There are 278 repondents (educators, educational personnel, committee). The analysis method involved SEM PLS and Smart PLS 2.0 as statistic test tools. The result showed that the participatory budgeting affected the school performances. The organizational commitment and leadership styles were able to moderate the effect of participatory budgeting on performances. The leadership styles focusing on the preference and skill of the subordinates became the main concern and the commitment of the members to the organization supported the performance of the schools.Â Keywords: Participatory Budgeting, Performance, Leadership Styles, Organizaional Culture, Organizational Commitment